Tax Analysis And Its Implications For The High Cost Of Education In The Procurement Of Training Aircraft - Suryono, Aji; Anwar , Chairil (Sinergi International Journal of Education, 2023)
The purpose of this study is to analyze the imposition of import taxes and import duties for training aircraft procurement and its implications for thehigh cost of education at Indonesian Aviation Polytechnic Curug and Aero Flyer Institute in 2017-2020. This study is a qualitative descriptive study with data collection techniques used are interviews, observations, documents and triangulation, so that the researcher can draw conclusions. The conclusion of import taxes imposition and import duties has a high influence in determining the high cost of flight schools. With the high cost of flight schools, it will affect people's interest in becoming a pilot. However, this is a burden that must be borne by the educational institution itself which in the end causes the high cost of pilot school to be charged to prospective pilot students. The imposition of import taxes includes Sales Tax on Luxury Goods, Income Tax and VAT because aircraft training are subject to these three tax components. These three components cause the high cost of pilot school. In this case, the government must immediately review the taxation policy for the procurement of aircraft training and educational institutions must also cooperate with various airline operators both at home and abroad to attract pilot graduates and this will increase the interest of the Indonesian people to become professional and reliable pilots.